2020
DOI: 10.3389/fonc.2020.01651
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Cervical Cancer and Attitude Toward Human Papillomavirus and Its Vaccine Among Ghanaians

Abstract: Background: Cervical cancer (CC) is the fourth most commonly diagnosed cancer among women. Ghana is a low-middle-income country with annual diagnosed cases of 3,151 and 2,119 deaths. The high prevalence rate of cervical cancer in Ghana is mainly due to ineffective preventive measures and insufficient knowledge about the disease. Therefore, our objective was to evaluate the level of knowledge and awareness of cervical cancer and attitude toward human papillomavirus and its vaccine among Ghanaians. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 43 publications
(67 reference statements)
3
25
2
Order By: Relevance
“…The questionnaires employed in this study is a modified version of the one used in our previous study after it was approved by experts ( 39 ). An advisory committee of two experts in research methodology, gynaecology and obstetrics, and oncology evaluated the questionnaire legitimacy and soundness prior to the pilot test.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires employed in this study is a modified version of the one used in our previous study after it was approved by experts ( 39 ). An advisory committee of two experts in research methodology, gynaecology and obstetrics, and oncology evaluated the questionnaire legitimacy and soundness prior to the pilot test.…”
Section: Methodsmentioning
confidence: 99%
“…Before the intervention, 8.9% of students responded that high parity could be a risk factor, and it can be compared with a 12% awareness reported in a study. 41 After the intervention, 44.4% of students indicated that high parity could be a risk factor; however, this score is extremely low compared to research conducted in Ghana, 38 owing to the country’s cultural differences, and high parity is very common.…”
Section: Discussionmentioning
confidence: 85%
“…Before the intervention, only 42.6% of research participants were aware of risk factors, which is low compared to a study conducted in Ghana, which found that 63.8% of participants were aware of cervical cancer risk factors. 38 At the base level, 57.4% of study respondents did not know any risk factors. This score is lower than a study done in Eastern Ethiopia, 24.2%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations